Mental health and stigmatization in today’s environment - Chorna Валентина (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the II Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to mental health and stigmatization in today’s environment.